Escala de dificultades percibidas para la conducción, hostilidad y extraversión: un análisis correlacional en conductores de Bogotá (2010)
In Colombia, there are very few works about associated factors to road-traffic accidentally. The aim of this research was both to explore psychometric properties of a perceived Difficulties to Conduction Scale (DCS) in Bogotá, in relation to several transit norms, and to study relationships between DCS with hostility, anger, extrovertion measures and bad practices of conduction: accidents and penalties. A non-randomized sample of bus, taxis and private cars conductors answered a questionnaire with this variables. Results showed a high internal reliability of DCS, a unique factor structure and relationships between higher EDC scores and higher hostility, anger, accidents and penalties. Extrovertion has an indirect influence in DCS.